Major storms influence on the morphological evolution of a hybrid spit-tidal flat system in Argentina - Guisado Pintado, Emilia (2023)
Sandy coastal systems are very dynamic systems in which morphological changes occur overdifferent time scales that ranges from hours to decades. However, it has been widely reported thatmajor storms are the main responsible of the most significant changes in short to medium timescales. Major storms have been defined using a variety of environmental variables, but they arenormally associated with high values of four main parameters: 1) Wave heights (Hs); 2) Duration(Du); or 3) Frequency (Fq); 4) Orientation (Or).In this study we aim to characterise types of major storms and to categorize morphologicalimpacts over a hybrid coastal system. The study site, known as Punta Rasa, is located in theSamborombón bay in the outer part of the Río de La Plata estuary (Argentina) and corresponds toa zone of interaction between a large sandy spit and a backwash tidal flat system. Methods usedcombine statistical analysis of wave climate time-series, analysis of wave energy patterns throughnearshore numerical modelling (SWAN) and comparison of pre- and post-storm morphologicalchanges using satellite images derived indexes (e.g. NDWI).Results allowed to characterise four types of major storms impacting the study area: High-EnergyStorms (HES), defined by an average storm Hs below the 1% exceedance (> 2.6 m), Long-LivedStorms (LLS) represented by an exceedance of the 1% of Du (> 60 hours), Storm Groups (SG) inwhich storm frequency is less than 6 days and Northeastern moderate storms (NMS) defined bytheir eastern, onshore oriented direction. Under HES and NSM storms erosional areas aredominant over depositional (62.34%), which most of the system showing shoreline retreat and agrowth of the end spit area. For LLS and SG storms the morphological impact varies alongshorewith a general flattens of the end spit (showing a ‘rounded-shape’ morphology) and erosionalhotspots over the southeastern coastal section.